Biometrics and ID Management COST 2101 European Workshop, BioID 2011, Brandenburg (Havel), Germany, March 8-10, 2011. Proceedings - Vielhauer, Claus; Dittmann, Jana.; Drygajlo, Andrzej; Juul, Niels Christian; Fairhurst, Michael C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed proceedings of the COST 2101 International Workshop, BIOID 2011, held in Brandenburg (Havel), Germany, in March 2011. The 25 revised full papers presented were carefully reviewed and selected from numerous submissions and are completed by an introduction on COST. The papers are organized in topical main sections on theory and systems, handwriting authentication, speaker authentication, face recognition, multibiometric authentication, and on biometrics and forensics.
Keywords: Computer science; Information storage and retrieval systems; Artificial intelligence; Computer vision; Optical pattern recognition; Biometrics; Computer Science; Biometrics; Pattern Recognition; Computer Imaging, Vision, Pattern Recognition and Graphics; Image Processing and Computer Vision; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).